Deep-ultraviolet near band-edge emissions from nano-polycrystalline diamond. Issue 1 (2nd January 2020) - Ishii, Ryota; Fukuta, Rei; Ishikawa, Fumitaro; Matsushita, Masafumi; Ohfuji, Hiroaki; Shinmei, Toru; Irifune, Tetsuo; Funato, Mitsuru; Kawakami, Yoichi
ABSTRACT: Deep-ultraviolet continuous-wave photoluminescence spectroscopy is performed for nano-polycrystalline diamond (NPD) synthesized by a high pressure high-temperature technique. NPD exhibits clear deep-ultraviolet emissions, which originate from intrinsic excitonic transitions assisted by a momentum-conserving phonon with a photon. Surprisingly, the peak emission energy is about 30 meV higher than that of the single-crystalline diamond. Raman scattering spectroscopy indicates that the energy difference should originate from the excitonic properties of the NPD and not the phonon. Hence, NPD has a large bandgap compared to single-crystalline diamond.